Komparasi Algoritme C4.5 Dan Naïve Bayes Dalam Klasifikasi Produk Zam–Zam Time Berdasarkan Tingkat Kepuasan Pelanggan - Martiyaningsih, Dwi Puspa; Ramadhani, Rima Dias; Dewi, Atika Ratna (Progresif: Jurnal Ilmiah Komputer, 2023)
The grouping of Zam-Zam Time products based on the level of customer satisfaction is carried out using the C4.5 and Naïve Bayes classification algorithms. Algorithm classification for Zam-Zam Time products is carried out to find out which products are classified as Best Selling or Less Selling. The purpose of this study is to measure and analyze the best algorithm for handling data on the level of customer satisfaction. Zam-Zam Time is classified as a best seller or not a best seller. The method used in this study was data preprocessing by distributing questionnaires and labeling taken from private or primary data from Zam-Zam Time itself as well as the results of a questionnaire of 400 customer respondents, then a classification analysis process was carried out. The results of the performance of the C4.5 Algorithm in the classification of Zam-Zam Time products are classified as Best Selling or Less Selling, namely with a Training data accuracy value of 98%, computation time of 0.003989458084106445 seconds, Testing data accuracy value of 96%, commutation time of 0.001993417739868164 seconds, with the 8th max_depth, and while Naïve Bayes Data Accuracy Value Training 90% computing time 0.0049860477447509766 seconds, Data Testing 85%, computing time 0.0019948482513427734 seconds.Keywords: Classification; Customer Satisfaction; C4.5 Algorithm; Naïve Bayes; Zam-Zam Time AbstrakPengelompokan produk Zam-Zam Time berdasarkan tingkat kepuasan pelanggan dilakukan menggunakan klasifikasi algoritme C4.5 dan Naïve Bayes. Klasifikasi algoritme pada produk Zam-Zam Time dilakukan untuk mengetahui produk tergolong laris atau kurang laris. Tujuan dari penelitian ini mengukur dan analisis algoritme terbaik dalam menangani data tingkat kepuasan pelanggan Zam-Zam Time tergolong laris atau kurang laris. Metode yang digunakan dalam penelitian ini adalah dilakukan preprocessing data dengan penyebaran kuesioner dan pelabelan yang diambil dari data privat atau primer dari Zam-Zam Time itu sendiri serta hasil kuesioner sebanyak 400 responden pelanggan, kemudian dilakukan proses analisis klasifikasi. Hasil kinerja Algoritme C4.5 dalam klasifikasi produk Zam-Zam Time tergolong Laris atau Kurang Laris yaitu dengan Nilai Akurasi data Training 98%, waktu komputasi 0.003989458084106445 detik, nilai akurasi data Testing 96%, waktu komutasi 0.001993417739868164 detik, dengan max_depth ke-8, sedangkan Naïve Bayes Nilai Akurasi data Training 90% waktu komputasi 0.0049860477447509766 detik, data Testing 85%, waktu komputasi 0.0019948482513427734 detik.Kata Kunci: Kepuasan Pelanggan; Algoritme C4.5; Naïve Bayes; Klasifikasi; Zam-Zam Time